Studi Evaluasi terhadap Efektivitas Sistem Pembinaan Sekolah Dasar melalui Gugus Sekolah - Bunyamin Maftuh (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: The objective of this research was to examine the implementation of the policy of proffesional guidance system for elementary schools’ teachers through schools force. The population were schools’ beurocracy, eductional practitioners, managers of schools force, and builders of schools force. The subjects were selected through porpusive sampling techniques. The data collection instruments were questionnaire, focus discussion group, interview, documentation study, and observation. The research results were: (1) in general school cluster performances in developing professionalism of elementary teachers were in moderate (enough) category, (2) the professionalism level of teachers who involved in school cluster-based teacher professional development was in less or low category, (3) teacher competencies in teacher learning processes in general were only in moderate category, which have not reached ideal quality, (4) student achievements were in good enough level in line with the quality of teaching learning process that was in moderate category.